Medication intake and its influence on salivary profile of geriatric outpatients in Cipto Mangunkusumo Hospital - Yuniardini Septorini Wimardhani; Winanda Annisa; Febrina Rahmayanti (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: It has been well documented that several diseases or conditions and their related medications could be the risk factors for several ailments found in the oral cavity. Increased usage of medication in elderly could have impact on quality of saliva that affects oral health, eventually cause deterioration in quality of life. Purpose: examine the salivary pH, buffering capacity, stimulated- and unstimulated salivary flow rate profile in elderly using medications. Methods: Seventy-six elderly were consented and agreed to participate in this study. Interview and medical record analysis were performed to get data about their health status, chronic use of medications and complaints related to xerostomia. Collection of unstimulated and stimulated saliva samples were completed in parallel with measurement of salivary pH and buffering capacity. Results: The mean salivary pH was moderately acidic while having low salivary buffering capacity. The mean unstimulated salivary flow rate (USSFR) was 0.24 ± 1.8ml/min and 41of subjects (53%) were classified hyposalivation, while the stimulated salivary flow rate (SSFR) was 0.86 ± 0.49ml/min and 31 (40%) classified hyposalivation. Number of drugs-induced xerostomia intake significantly correlated with the reduction in the USSFR of subjects (p<0.0001), however it was not the case with salivary pH and buffering capacity (p>0.05). It also showed correlation with complaints related to xerostomia. The mean USSFR did not correlate with xerostomia complaints. Conclusion: Medications intake influenced salivary profile and had more effect in changes in xerostomia complaints and salivary quantity than to salivary pH and buffering capacity in Indonesian elderly population.Latar belakang: Telah lama diketahui bahwa beberapa penyakit atau kondisi sistemik dan medikasinya dapat menjadi faktor resiko terjadinya beberapa kelainan dalam rongga mulut. Meningkatnya penggunaan medikasi sistemik pada lansia dapat mempengaruhi kualitas saliva sehingga berpengaruh pada kesehatan mulut yang akhirnya menyebabkan menurunnya kualitas hidup. Tujuan: Mengetahui profil pH saliva, kapasitas dapar, laju aliran saliva terstimulasi (LAST) dan tanpa stimulasi (LASTS) pada lansia yang mendapatkan medikasi sistemik. Metode: Tujuh puluh enam lansia telah menandatangani inform consent dan setuju untuk berpartisipasi. Wawancara dan analsis rekam medis dilakukan untuk mendapatkan data tentang status kesehatan, penggunaan medikasi sistemik jangka panjang dan keluhan xerostomia. Pengumpulan saliva tanpa stimulasi dan terstimulasi dilakukan bersama-sama dengan pengukuran pH dan kapasitas dapar. Hasil: pH saliva subyek adalah berada dalam kelompok asam sedang dengan kapasitas dapar yang rendah. Rerata LASTS adalah 0,24 ± 1,8ml/menit dan 41 subyek (53%) mengalami hiposalivasi, sementara LAST adalah 0,86 ± 0,49ml/menit dan 31 subyek (40%) mengalami hiposalivasi. Jumlah medikasi yang dapat menginduksi xerostomia secara bermakna berhubungan dengan penurunan LASTS (p < 0,0001), namun tidak demikian dengan pH dan kapasitas dapar (p>0,05). Medikasi sistemik juga berhubungan dengan keluhan yang terkait xerostomia. Rerata LASTS tidak berhubungan dengan keluhan xerostomia. Kesimpulan: Medikasi sistemik pada populasi lansia Indonesia mempengaruhi profil saliva dan mempunyai pengaruh yang lebih besar pada keluhan xerostomia dan kuantitas saliva dibandingkan pH dan kapasitas dapar.